ANALISA KEGAGALAN RODA GIGI MATAHARI SWING DRIVE PADA EXCAVATOR CATERPILLAR 349 D - Achmad Kusairi Samlawi; Muhammad Zaini (INFO-TEKNIK, 2019)
The study focused on analyzing the failure of the sun gear section of the swing drive excavator, where there has been a failure in operation. The gears are predominantly damaged in certain areas while other areas appear to have minimal failure. To answer the cause of failure of the gear, 3 stages of testing are carried out, namely; macro observation, chemical composition test and hardness test and loading simulation. The results of this test are that failure occurs due to case crushing caused by residual stresses under the surface of the gears, the detached surface and pinnion conditions exposed to the soft parts become more vulnerable so that scoring occurs causing macrowelding.